Exploring drug utilization patterns, healthcare resource utilization, and epidemiology of rheumatoid arthritis in Colombia: a retrospective claims database study - Daniel G. Fernández-Ávila; Monica Betancur; Amira Kronfly; Edwin Jáuregui (BMC Rheumatology)
Abstract Background In Colombia, there is a lack of recent real- word studies that provide information on the epidemiology and healthcare resource utilization (HCRU) of rheumatoid arthritis (RA) at national level. Methods To describe the burden of RA in Colombia, focusing on trends in drug utilization patterns, healthcare resource utilization (HCRU), and the epidemiology of adult patients diagnosed with RA between January 2017 and December 2022. This retrospective descriptive study used real-world data obtainedfrom a national claim database, SISPRO (Sistema de Información para la Protección Social). We included registries of adult patients diagnosed with RA between 2017 and 2022. We estimated the age-standardized incidence and prevalence of RA each year, drug utilization patterns for disease-modifying antirheumatic drugs (DMARDs) and glucocorticoids, rates of medical consultations, emergency room visits, and hospitalizations, and associated comorbidities and healthcare-related and pharmacy-related costs. Results Overall, 327,430 unique patients with RA between 2017 and 2022 were included in the analysis, comprising 94,093 incident cases and 722,569 prevalent cases. The age-standardized incidence of RA ranged between 34.7 and 51.4 per 100,000 inhabitants, and the age-standardized prevalence ranged between 0.282 and 0.382 per 100 inhabitants between 2017 and 2022. The proportion of patients prescribed conventional synthetic DMARDs and biologic DMARDs decreased over the study period, from 39.23% in 2017 to 28.61% in 2021 and from 6.07% in 2017 to 3.72% in 2021, respectively. The proportion of patients prescribed targeted synthetic DMARDs increased from 0.9% in 2017 to 1.8% in 2021. The rate of medical consultations increased over the study period (from 2,406.6 in 2017 to 3,354.2 per 1,000 patients with RA in 2022). Consultation costs were the largest among all-cause annual healthcare-related costs. Conclusion This study described the heavy burden of RA in Colombia with an increasing incidence of RA, and significant healthcare resource utilization and associated costs. Patients with RA in the country are increasingly able to access consultations with specialists and receive advanced therapies. However, there remains a need for efforts to facilitate treatment among this population. These findings emphasize the importance of tailoring RA management strategies to the local context.